Prevalence of periodontitis based on the american academy of periodontology and European federation of periodontology 2017 classification scheme in patients visiting a tertiary care center in New Delhi - An epidemiological study - Kirti Chawla; Madhuri Alankar Sawai; Ashu Bhardwaj; Zeba Jafri; Nishat Sultan (Wolters Kluwer Medknow Publications, 2024)
Introduction: Periodontitis is one of the major reasons for tooth loss in adults. Therefore, it is important to know the true prevalence of the disease. Aim: This study was designed to find out the prevalence of periodontitis in Delhi state based on the American Academy of Periodontology (AAP) and European Federation of Periodontology (EFP) 2017 classification scheme. Materials and Methods: It was a descriptive cross-sectional study involving 2200 patients. Periodontal data were collected using the Community Periodontal Index of Treatment Needs-Epidemiological probe. Periodontal disease was diagnosed with the 2017 AAP and EFP definitions and classifications. Results: Of the study population, 93.2% had no detectable clinical attachment loss (CAL), 34.8% (n = 52) were classified with Stage I, 34.8% (n = 52) with Stage II, 16.8% (n = 25) with Stage III, and none with Stage IV periodontitis. Grade A was the predominant grade, being diagnosed in 50% of the periodontitis cases. The majority of cases (62%) demonstrated generalized periodontitis. Conclusion: The new periodontal disease classification system introduced in 2017 has provided a comprehensive description of periodontal disease which can classify the periodontal disease on the basis of various factors. Based on this, our study reported a maximum number of Stage I and II periodontitis patients.